Pengaruh Pemotivasian terhadap Efektivitas Kerja Pegawai di Dinas Pendidikan Provinsi Riau - SADAD, ABDUL (Jurnal Kebijakan Publik, 2011)
Qualified human resources is one important component that will determine the success of anorganization in achieving the goals set earlier. To achieve these objectives required good order of existenceand the existence of the organization can be maintained and improved. Efforts that can be used in managementhuman resources is through motivational conducted by the leadership. The method used in this research issurvey method with the explanatory data collection techniques using questionnaires as the main instrument(primary data), in addition to interviews, and observation. While analyzing the data using path analysis.The results indicate a motivating influence on the effectiveness of employees working in Riau ProvinceEducation Department. These effects indicate that the effectiveness of the work will be increased if themotivating factor that external factors and internal factors implemented as a whole, so that employees havethe sincerity in carrying out their work because they get real attention.Keywords: Achieving, external factors, and internal factors.